Peran Komite Sekolah Dalam Kebijakan Sekolah Di SMP Islam Sudirman Ambarawa Kabupaten Semarang - Riyono, Joko; , Dr. Suyatmini, M.Si; , Dr. Sumardi, M.Si (2015)
The purpose of the research are to discribe: (1). The role of school's committee to principle of planning programme, (2). The committee's responsibility to implementation of programme, (3). The role of committee to the monitoring of principle at SMP Islam Sudirman Ambarawa Semarang Regency. This research is a qualitative research and its subjects are principal, school committee, teachers, students as well as their parents, in SMP Islam Sudirman Ambarawa, Semarang regency. The methods of data collection are by using interview, observation and documentation. The qualitative data analysis technique uses interactive model analysis technique. The steps of data analysis consists of data reduction, data processing and conclusion. The data validity consists of internal validity, external validity, dependant and assurance. The results of the reseach are : (1). The role of school's committee : to give approval of programme's planning, to give advices to the each of sector's personel, to legalize RAPBS, RKTSP, RPS to be APBS, KTSP, RPS; (2). The role of committee in implementation are : to gain the coorporation with the school's stake holder, to arrange halal-bihalal, to arrange routine considerable; (3). The committee's role is to control reports of : the implementation of KBM (Teaching Learning Activities), study tour, PMR, KIR, supplying goods, supplying of multimedia devices, use of finances. Keywords: committee characteristic; school committee; school policy, ABSTRAK Tujuan Penelitian ini adalah untuk mendeskripsikan karakteristik: (1) peran komite sekolah terhadap perencanaan program kebijakan, (2) tanggung jawab komite terhadap pelaksanaan program, (3) peran komite terhadap pengawasan kebijakan di SMP Islam Sudirman Ambarawa Kabupaten Semarang. Penelitian ini adalah penelitian kualitatif, subjek penelitiannya adalah kepala sekolah, pengurus komite, guru, siswa, dan wali siswa di SMP Islam Sudirman Ambarawa Kabupaten Semarang. Metode pengumpulan data dengan menggunakan teknik interview, observasi, dan dokumentasi. Teknik analisis data kualitatif menggunakan teknik analisis model interaktif. Tahap-tahap analisis data meliputi reduksi data, penyajian data, dan pengambilan kesimpulan. Keabsahan data meliputi validitas internal, validitas eksternal, ketergantungan, dan kepastian. 2 Hasil dari penelitian ini: 1) peran komite sekolah dalam perencanaan : memberi persetujuan pembuatan rencana program, memberi pertimbangan pada personil masing-masing bidang, mengesahkan RAPBS,RKTSP, RPS menjadi APBS,KTSP dan RPS; 2) peran komite dalam pelaksanaan: mengadakan kerjasama dengan stake holder, mengadakan kegiatan halal bihalal, dan pengajian rutin. 3) peran komite dalam pengawasan diantaranya mengontrol laporan: pelaksanaan KBM, kegiatan karyawaisata, PMR, KIR, pengadaan barang, pengadaan alat multi media, penggunaan keuangan.